Variation of vitamin B contents in maize inbred lines: Potential genetic resources for biofortification - Safiul Azam, Fardous Mohammad; Lian, Tong; Liang, Qiuju; Wang, Weixuan; Zhang, Chunyi; Jiang, Ling (Frontiers in Nutrition, 2022)
Vitamin B and its derivatives possess diverse physiological functions and are essential micronutrients for humans. Their variation in crops is important for the identification of genetic resources used to develop new varieties with enhanced vitamin B. In this research, remarkable variations were observed in kernels of 156 maize inbred lines, ranging from 107.61 to 2654.54 μg per 100 g for vitamin B1, 1.19 to 37.37 μg per 100 g for B2, 19.60 to 213.75 μg per 100 g for B3, 43.47 to 590.86 μg per 100 g for B5, and 138.59 to 1065.11 μg per 100 g for B6. Moreover, there was a positive correlation between vitamin B1, B5 and B6, and between pyridoxine and pyridoxamine. Several inbred lines were identified as good sources of vitamin B and promising germplasms for maize breeding. The present study can assist maize breeders with vitamin B biofortification to offer people nutritious foods.